The Development Of Web-Based Application For Reporting Status Component At Aircraft Maintenance, Repair, And Overhaul (MRO) Industry - Rayhan Dhiya Rista; Jansen Wiratama (G-Tech: Jurnal Teknologi Terapan, 2023)
PT GMF Aero Asia, Tbk, has an application that integrates all needs in terms of maintenance and management, especially in component status, using SAP Swift tools. However, SAP Swift has several areas for improvement, namely repeated findings due to limitations on component data repair in SAP SWIFT, preparation for each status done manually, and inability to quickly address customer needs for increased audit needs. Therefore, we need a website-based application that can display status automatically, has capabilities in data processing, displays notifications of differences between previous and new data, and can receive data sent from SAP Swift. The Front-End design of this application uses the vue.js framework, and the Back-End design uses Nest.js, which is integrated with PostgreSQL as a DBMS. In the final stage, before users use this application, a REST API test is carried out using POSTMAN with excellent test results according to user scenarios.